Factors that influence fatigue status in Canadian university swimmers - Kenned, M. D.; Tamminen, K. A.; Holt, N. L. (Journal of Sports Sciences, 2013)
The overall purpose of this two-part study was to examine factors that influenced fatigue status in university level swimmers. Participants were 25 swimmers (14 male, 11 female) from one university swim team. A mixed methods approach was used. Quantitative data were collected using an orthostatic heart rate test and self-report questionnaire at multiple time points throughout a competitive season. Qualitative data were collected via focus groups conducted at the end of the season. Analysis of the quantitative data indicated high levels of accumulated physiological and psychological fatigue that improved with increased recovery. Specifically, heart rate indices, form, feeling, and energy level improved during taper periods and worsened during and immediately after intensive training blocks. Analysis of the qualitative data revealed that one factor (flexible structure of training programme) had a positive influence on athletes` fatigue while two factors (teammate expectations and balancing school, work, and sleep) had a negative influence on athletes` fatigue.